Novel Data Linkages to Characterize Palliative and End-of-Life Care: Challenges and Considerations - McDermott, Cara L. (J Pain Symptom Manage, 2019)
CONTEXT: Working groups have called for linkages of existing and diverse databases to improve quality measurement in palliative and end-of-life care, but limited data are available on the challenges of using different data sources to measure such care. OBJECTIVES: To assess data concordance obtained from different sources in a novel linkage of death certificates, electronic health records (EHR), cancer registry data, and insurance claims for patients who died with cancer. METHODS: We joined a database of Washington State death certificates and EHR to a data repository of commercial health plan enrollment and claims files linked to registry records from Puget Sound Cancer Surveillance System. We assessed care in the last month including hospitalizations, ICU admissions, emergency department (ED) visits, imaging scans, radiation, and hospice, plus chemotherapy in the last 14 days. We used a chi-square test to compare differences between healthcare in EHR and claims. RESULTS: Records of hospitalization, ICU, and ED use were 33%, 15% and 33% lower in EHR versus claims. Radiation, hospice, and imaging were 6%, 14% and 28% lower in EHR, but chemotherapy was 4% higher compared to claims. These differences were statistically different for hospice (p<0.02), hospitalization, ICU, ER, and imaging (all p<0.01) but not radiation (p=0.12) or chemotherapy (p=0.29). CONCLUSION: We found substantial variation between EHR and claims for end-of-life healthcare use. Reliance on EHR will miss some healthcare use while claims will not capture the complex clinical details in EHR that can help define the quality of palliative care and EOL healthcare utilization.